Current Status of The Application of Different Sutures For Meniscus - Chen, Yuye (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The meniscus plays a critical role in preserving the knee’s normal physiological function, which includes proprioception, stabilising the joint, nourishing and lubricating it, increasing the contact area of the articular surfaces and the match between the tibia and femur, and bearing distributed stress and shock. When people are exposed to external forces that cause their knees to twist, meniscus injury may result. However, if the meniscus is removed for resection, the likelihood of developing osteoarthritis in the knee joint increases. As arthroscopy technology has advanced, the goal of treating meniscus injuries is to keep as much of the damaged meniscus intact as feasible while also attempting to repair the meniscus by suturing as much of it as possible, if it is possible. In order to provide some reference for the clinical research of arthroscopic suture meniscus, this article presents the structure of the meniscus, focuses on various suture techniques for the treatment of arthroscopic meniscus injuries, and evaluates their benefits and drawbacks, as well as the proper suture techniques for various injuries.